Empowering Indonesian University Students’ Spoken English dnd Self-Confidence Through Adaptive Learning Materials - Ramasari, Maria; Ardayati, Ardayati (JURNAL PERSPEKTIF PENDIDIKAN, 2025)
English proficiency, particularly in speaking, remains a major challenge for university students in Indonesia due to the lack of adaptive learning resources that align with learners' individual needs and contexts. In response to this issue, this research aims to empower Indonesian university students’ spoken English skills and self-confidence by developing adaptive learning materials in the form of a communicative English textbook. This study employed Research and Development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) as modified by Dick & Carey. The analysis phase involved needs assessment through interviews and observations. In the design phase, the textbook structure and learning objectives were formulated. The development phase focused on producing and validating the textbook with input from experts in language, material, and instructional media. The implementation stage consisted of one-to-one trials, small group testing, and large group testing involving university students. Finally, the evaluation phase assessed the validity, practicality, and effectiveness of the developed textbook. The results of this study indicate that the textbook is valid based on expert validation, practical according to lecturers’ and students’ responses, and effective in improving students' speaking performance and confidence. In conclusion, the developed materials provide meaningful, student-centered activities that reflect real communication scenarios, fostering both linguistic competence and affective growth. This research contributes to innovative textbook development within the Indonesian higher education context.